Conductive polyester fiber as well as preparation method and application thereof

Through the control of the zero-shear viscosity difference between the leather core structure and the polyamide elastomer, the enrichment of conductive carbon black on the fiber surface is promoted, and the problems of insufficient durability and conductivity of conductive polyester fibers are solved, and the spinning and strength of the fibers are improved.

CN120273061AActive Publication Date: 2025-07-08JIANGSU GUOWANG HIGH TECH FIBER CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510772179.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-11
Publication Date
2025-07-08
Estimated Expiration
2045-06-11

AI Technical Summary

Technical Problem

现有导电聚酯纤维在使用过程中耐久度不足,导电性能容易下降,且为了追求高导电性而影响纤维的可纺性和强度。

Method used

The conductive polyester fiber adopts a leather-core structure, the core layer is the first polyethylene terephthalate, and the cortex is the second polyethylene terephthalate, the first polyamide elastomer and the conductive carbon black masterbatch. By controlling the zero-shear viscosity difference of the polyamide elastomer, it is enriched on the fiber surface during the spinning process, and combined with the crystallization of the polyamide hard section, it promotes the enrichment of conductive carbon black in the amorphous area.

Benefits of technology

With less conductive material addition, the conductivity stability and mechanical properties of the fiber are improved, and the fiber is spinable and durable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a conductive polyester fiber and a preparation method and application thereof, and relates to the field of functional fibers.The conductive polyester fiber is of a skin-core structure, a core layer component comprises first polyethylene glycol terephthalate, and a skin layer component comprises second polyethylene glycol terephthalate, a first polyamide elastomer and conductive carbon black masterbatch; the conductive carbon black master batch comprises a second polyamide elastomer and conductive carbon black; the zero-shear viscosity difference value of each polyamide elastomer and each polyethylene glycol terephthalate is controlled, so that the melt viscosity of the polyamide elastomer is lower than that of the polyethylene glycol terephthalate, and the low-viscosity polyamide elastomer is easy to diffuse to the surface of the fiber in the spinning process to drive the conductive carbon black to be enriched on the surface of the fiber; a hard segment in the polyamide elastomer can be crystallized in the stretching and drafting process, so that the conductive carbon black is promoted to be transferred to an amorphous region and enriched; practice shows that the fiber disclosed by the invention not only has excellent conductivity, but also has properties such as lasting stability and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of functional fibers, and particularly to a conductive polyester fiber, a preparation method thereof, and an application thereof. Background Art

[0002] Polyethylene terephthalate fiber (polyester fiber, abbreviated as PET fiber) is one of the synthetic fibers with relatively large output and wide application at present. It has advantages such as good strength, chemical corrosion resistance, light resistance, and heat resistance, and occupies a crucial position in the fields of textile clothing, home textiles, etc. However, at present, the polyester fiber market is highly competitive, with serious homogenization and low net profit, bringing great challenges to polyester fiber production enterprises.

[0003] To meet the diverse needs of the market, developing functional polyester fibers is one of the effective ways to enhance the competitiveness of enterprises. For example, in the fields of safety protection, camouflage reconnaissance materials, energy harvesting, smart wearables, etc., developing a conductive polyester fiber with properties such as softness, good conductivity, and bend recoverability will have good application prospects. However, the current conductive polyester fibers still have the following problems more or less: (1) There is insufficient durability, and the conductivity is likely to decrease significantly during use. For example, Patent CN112981959A provides a sol-type conductive polyester fiber, which overcomes the surface polarity of polyester fibers, uses sericin to finish polyester fabrics, and incorporates Fe 3+ to improve its antistatic / conductive performance. However, the durability of the sol layer is poor, which will cause the conductivity of the fiber to decrease during use. Similarly, using methods such as electroplating and electroless plating to construct a conductive layer on the surface of polyester fibers also faces the problem of insufficient conductive durability.

[0004] (2) There is insufficient conductivity, or too much conductive material is added in order to pursue high conductivity, which in turn causes obvious degradation of the spinnability, strength and other properties of the fiber, and is not conducive to practical applications. For example, Patent CN107354534A uses a composite spinning process to prepare a core-shell structured conductive composite fiber. The core layer is fiber-grade polyester, and the skin layer is a low-melting polymer and a conductive masterbatch. The conductive material is evenly dispersed in the radial direction of the fiber skin layer. To ensure a certain conductivity, more conductive substances can only be added to form a contact resistance and build a conductive path, which to a certain extent affects the spinnability and strength of the fiber.

[0005] Therefore, developing a conductive polyester fiber that not only has excellent conductivity but also has properties such as lasting stability and excellent mechanical properties has become a technical challenge that urgently needs to be overcome. Summary of the Invention

[0006] The object of the present invention is to overcome one or more deficiencies in the prior art and provide an improved conductive polyester fiber, which can have excellent electrical conductivity, as well as properties such as lasting stability and excellent mechanical properties, and the addition amount of the conductive material is relatively small.

[0007] The present invention also provides a preparation method of the conductive polyester fiber and its applications in preparing safety protection materials, camouflage and reconnaissance materials, energy harvesting materials, and intelligent wearable materials.

[0008] To achieve the above object, a technical solution adopted by the present invention is: A conductive polyester fiber, the conductive polyester fiber has a skin-core structure, the core layer component in the skin-core structure includes a first polyethylene terephthalate, and the skin layer component includes a second polyethylene terephthalate, a first polyamide elastomer, and a conductive carbon black masterbatch. The raw materials of the conductive carbon black masterbatch include a second polyamide elastomer and conductive carbon black, and the conductive carbon black has a terminal carboxyl group; Under the same test temperature condition, the zero shear viscosity of the first polyamide elastomer is denoted as η1, the zero shear viscosity of the second polyamide elastomer is denoted as η2, the zero shear viscosities of the first polyethylene terephthalate and the second polyethylene terephthalate are both denoted as η3, and the zero shear viscosity is measured by a steady-state shear rheological experiment, with the unit of Pa·s; when the test temperature is 275 - 290 °C, η1, η2, and η3 satisfy the following conditions: 35 Pa·s ≤ η3 - η1 ≤ 280 Pa·s, 50 Pa·s ≤ η3 - η2 ≤ 300 Pa·s.

[0009] According to some preferred aspects of the present invention, under the same test temperature condition, the zero shear viscosity of the first polyamide elastomer is greater than or equal to the zero shear viscosity of the second polyamide elastomer, which is more conducive to the enrichment of conductive carbon black on the fiber surface.

[0010] In some preferred embodiments of the present invention, the number average molecular weight of the first polyamide elastomer is 18,000 - 20,000 g / mol.

[0011] In some preferred embodiments of the present invention, the number average molecular weight of the second polyamide elastomer is 15,000 - 18,000 g / mol.

[0012] According to some preferred aspects of the present invention, under the same test temperature condition, the zero shear viscosity of the first polyethylene terephthalate is the same as the zero shear viscosity of the second polyethylene terephthalate.

[0013] In some preferred embodiments of the present invention, the number-average molecular weight of the first polyethylene terephthalate and the number-average molecular weight of the second polyethylene terephthalate are 20,000 - 30,000 g / mol respectively.

[0014] According to some preferred aspects of the present invention, the first polyamide elastomer and the second polyamide elastomer are respectively polyether-based polyamide elastomers.

[0015] In the present invention, compared with polyester-based polyamide elastomers, using polyether-based polyamide elastomers can endow the fibers with better flexibility, the fiber feel is softer and more comfortable, and it can also improve the performance in low-temperature environments, enabling the fibers to still maintain good elasticity and flexibility in low-temperature environments, and not easily becoming hard or brittle. In addition, the water resistance and dyeing performance are also improved. It is analyzed that the ether bonds in the system play a beneficial anti-hydrolysis effect, and the relatively high polarity makes it easier to interact with dye molecules, thereby improving the dyeing performance.

[0016] Furthermore, the polyether-based polyamide elastomer is composed of a crystalline hard segment and an amorphous soft segment. The crystalline hard segment is polycaprolactam with a number-average molecular weight of 3,000 - 4,000 g / mol, and the amorphous soft segment is polyethylene glycol with a number-average molecular weight of 4,000 - 5,000 g / mol.

[0017] In some preferred embodiments of the present invention, based on 100 parts of the total amount of the cortical component, the second polyethylene terephthalate accounts for 40 - 50 parts, the first polyamide elastomer accounts for 15 - 20 parts, and the conductive carbon black masterbatch accounts for 30 - 45 parts.

[0018] According to some preferred aspects of the present invention, based on 100 parts of the total amount of the conductive polyester fiber, the cortical component accounts for 20 - 50 parts, and the core component accounts for 50 - 80 parts.

[0019] In some embodiments of the present invention, the conductive carbon black masterbatch is prepared by mixing and extruding the second polyamide elastomer and conductive carbon black.

[0020] According to some preferred and specific aspects of the present invention, the particle size of the conductive carbon black is 30 - 200 nm.

[0021] According to some preferred aspects of the present invention, by mass percentage, in the raw materials of the conductive carbon black masterbatch, the conductive carbon black accounts for 40% - 60%.

[0022] In some embodiments of the present invention, the volume resistivity of the conductive polyester fiber is 30 - 10 4Ω·cm, with a fineness of 1 to 10 dtex, a breaking strength greater than 3.5 cN / dtex, and a breaking elongation of 15% to 35%.

[0023] Another technical solution provided by the present invention: A method for preparing the conductive polyester fiber described above, the preparation method comprising: using a melt spinning process to spin the core component and the skin component into a core-sheath structured conductive polyester fiber, wherein the process parameters of the spinning and forming include: the melting and extrusion temperature of the core component is 285 to 300 °C, the melting and extrusion temperature of the skin component is 270 to 285 °C, the spinning pack temperature is 275 to 290 °C, the hot drawing temperature is 140 to 160 °C, and the hot drawing ratio is 5 to 8 times.

[0024] Another technical solution provided by the present invention: An application of the conductive polyester fiber described above in preparing safety protection materials, camouflage and reconnaissance materials, energy harvesting materials, and intelligent wearable materials.

[0025] In the present invention, the "first" and "second" in the first polyethylene terephthalate, the second polyethylene terephthalate, the first polyamide elastomer, and the second polyamide elastomer have no sequential order, and are only used to distinguish the polyethylene terephthalate or polyamide elastomer used in different components.

[0026] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: Based on the defects of the current conductive polyester fibers, such as insufficient durability, insufficient conductivity, or reduced spinnability and strength of the fibers in pursuit of high conductivity, the present invention innovatively provides an improved conductive polyester fiber, which has a skin-core structure, and uses a second polyethylene terephthalate, a first polyamide elastomer, and a conductive carbon black masterbatch (containing a second polyamide elastomer and a conductive carbon black containing a carboxyl group) as the skin layer component, and uses the first polyethylene terephthalate as the core layer component, and controls the zero shear viscosity difference between each polyamide elastomer and each polyethylene terephthalate, so that the melt viscosity of the polyamide elastomer is lower than the melt viscosity of the polyethylene terephthalate. During the spinning process, under the action of the shear and stretching flow field, the low-viscosity polyamide elastomer is easily Diffusion on the fiber surface drives the conductive carbon black to be enriched on the fiber surface (during melt spinning, the system is in a high-temperature molten state, the thermal motion of the molecules intensifies, the polyamide elastomer molecules with low viscosity are easier to move in the melt, and can overcome the intermolecular forces to diffuse to the fiber surface. In addition, the polyamide elastomer with low viscosity and polyethylene terephthalate are thermodynamically immiscible, which will produce microphase separation and migrate to the fiber surface. Through the interaction between the amide bond and the carboxyl group on the conductive carbon black, the conductive carbon black is enriched on the fiber surface). At the same time, the polyamide hard segment in the polyamide elastomer will crystallize during the stretching and drawing process (accompanied by cooling). In the crystallized state, under the volume exclusion of the crystals, the conductive carbon black will be promoted to transfer to the amorphous region and enrich in the amorphous soft segment area. Taking into account the combined effects of the above aspects, in the fiber of the present invention, the conductive carbon black is more concentrated and the overlap is more sufficient, so that better or even better conductive performance can be achieved with a smaller addition amount, thereby significantly reducing the amount of conductive filler added, while also reducing the impact on the strength of the fiber, and the fiber has good spinnability and long-term stability. DETAILED DESCRIPTION

[0027] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0028] Unless otherwise specified in the following examples, all raw materials are purchased from commercial sources or prepared by conventional methods in the art. In the following, conductive carbon black is purchased from Cabot, brand Vulcan® XC72R (oxidation modified type), which contains terminal carboxyl groups.

[0029] Example 1: This example provides a conductive polyester fiber and its preparation method. The conductive polyester fiber has a skin-core structure. The core layer component in the skin-core structure is the first polyethylene terephthalate, and the skin layer component is composed of the second polyethylene terephthalate, the first polyamide elastomer, and a conductive carbon black masterbatch; Calculated based on the total mass of the conductive polyester fiber being 100%, the skin layer component accounts for 20%, and the core layer component accounts for 80%; Calculated based on the total mass of the skin layer component being 100%, the second polyethylene terephthalate accounts for 40%, the first polyamide elastomer accounts for 15%, and the conductive carbon black masterbatch accounts for 45%; The raw materials of the conductive carbon black masterbatch are composed of the second polyamide elastomer and conductive carbon black. By mass percentage, in the raw materials of the conductive carbon black masterbatch, conductive carbon black accounts for 40%.

[0030] Both the first polyethylene terephthalate and the second polyethylene terephthalate are produced by Jiangsu Guowang Gaoke Fiber Co., Ltd., and the number average molecular weight is 20000 g / mol; the first polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the brand number 4050 and the number average molecular weight of 20000 g / mol; the second polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the brand number 3060 and the number average molecular weight of 15000 g / mol; The conductive carbon black masterbatch is prepared by the following method: The second polyamide elastomer (brand number 3060) is dried at 100 °C until the moisture content is less than 50 ppm, and then pre-high-speed mixed with conductive carbon black Vulcan® XC72R (oxidative modification type), and then melt-blended and extruded through a twin-screw extruder, and water-cooled pelletized to obtain the conductive carbon black masterbatch. Among them, the temperatures of the I - VII zones of the twin-screw extruder are 175 °C, 180 °C, 205 °C, 205 °C, 203 °C, 200 °C, and 195 °C respectively.

[0031] The preparation method of the conductive polyester fiber includes: The first polyethylene terephthalate and the second polyethylene terephthalate are dried in a low dew point drying oven at 165 °C until the moisture content is less than 50 ppm; the first polyamide elastomer and the conductive carbon black masterbatch are dried in a low dew point drying oven at 120 °C until the moisture content is less than 50 ppm; The dried first ethylene terephthalate serves as the core layer component and is melted by a screw extruder I (the temperatures in zones I to IV are 285 °C, 288 °C, 286 °C, and 286 °C respectively), and is metered and extruded by a metering pump I (the temperature of the metering pump is 286 °C); the dried second polyethylene terephthalate, the first polyamide elastomer, and the conductive carbon black masterbatch are the skin layer components and are melted by a screw extruder II (the temperatures in zones I to IV are 270 °C, 274 °C, 272 °C, and 272 °C respectively), and are metered and extruded by a metering pump II (the temperature of the metering pump is 272 °C). The melt of each component is extruded through a skin-core composite spinning component (the temperature of the component is 275 °C. Among them, under this temperature condition, the zero-shear viscosity of the second polyethylene terephthalate is 50 Pa·s higher than that of the second polyamide elastomer, and the zero-shear viscosity of the second polyethylene terephthalate is 38 Pa·s higher than that of the first polyamide elastomer). After being cooled by side blowing at 20 °C with a wind speed of 0.6 m / s, it undergoes bundling and oiling, and successively passes through pre-drawing (the temperature of the first hot roller is 140 °C, the speed is 800 m / min, the second hot roller is 140 °C, the speed is 1200 m / min), main drawing (the temperature of the third hot roller is 145 °C, the speed is 4000 m / min), and heat setting (the temperature is 140 °C, the speed is 4000 m / min), and finally is wound at 4050 m / min to produce conductive polyester fibers.

[0032] Example 2: This example provides a conductive polyester fiber and its preparation method. The conductive polyester fiber has a skin-core structure. The core layer component in this skin-core structure is the first polyethylene terephthalate, and the skin layer component is composed of the second polyethylene terephthalate, the first polyamide elastomer, and the conductive carbon black masterbatch; Based on the total mass of the conductive polyester fiber being 100%, the skin layer component accounts for 30%, and the core layer component accounts for 70%; Based on the total mass of the skin layer component being 100%, the second polyethylene terephthalate accounts for 42%, the first polyamide elastomer accounts for 18%, and the conductive carbon black masterbatch accounts for 40%; The raw materials of the conductive carbon black masterbatch are composed of the second polyamide elastomer and conductive carbon black. In terms of mass percentage, conductive carbon black accounts for 45% in the raw materials of the conductive carbon black masterbatch.

[0033] Both the first polyethylene terephthalate and the second polyethylene terephthalate are produced by Jiangsu Guowang Gaoke Fiber Co., Ltd., and the number-average molecular weight is 23000 g / mol; the first polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the brand number 6060 and the number-average molecular weight of 19500 g / mol; the second polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the brand number 3050 and the number-average molecular weight of 16000 g / mol; The conductive carbon black masterbatch is prepared by the following method: The second polyamide elastomer (grade 3050) is dried at 100 °C until the moisture content is less than 50 ppm, and then pre-high-speed mixed with conductive carbon black Vulcan® XC72R (oxidatively modified type), and then melt-blended and extruded through a twin-screw extruder, and water-cooled pelletized to obtain the conductive carbon black masterbatch. Among them, the temperatures of the I~VII zones of the twin-screw extruder are 178 °C, 185 °C, 210 °C, 210 °C, 208 °C, 205 °C, and 200 °C respectively.

[0034] The preparation method of the conductive polyester fiber includes: The first polyethylene terephthalate and the second polyethylene terephthalate are respectively dried in a low dew point drying oven at 165 °C until the moisture content is less than 50 ppm; the first polyamide elastomer and the conductive carbon black masterbatch are dried in a low dew point drying oven at 120 °C until the moisture content is less than 50 ppm; The dried first polyethylene terephthalate is used as the core layer component and melted through screw extruder I (the temperatures of the I~IV zones are 285 °C, 292 °C, 290 °C, and 290 °C respectively), and metered and extruded through metering pump I (the temperature of the metering pump is 290 °C); the dried second polyethylene terephthalate, the first polyamide elastomer, and the conductive carbon black masterbatch are used as the skin layer components and melted through screw extruder II (the temperatures of the I~IV zones are 273 °C, 280 °C, 278 °C, and 278 °C respectively), and metered and extruded through metering pump II (the temperature of the metering pump is 278 °C). The melt of each component is extruded through a skin-core composite spinning component (the temperature of the component is 280 °C, where, under this temperature condition, the zero-shear viscosity of the second polyethylene terephthalate is 93 Pa·s higher than that of the second polyamide elastomer, and the zero-shear viscosity of the second polyethylene terephthalate is 71 Pa·s higher than that of the first polyamide elastomer), cooled by side blowing at 18 °C with a wind speed of 0.65 m / s, and then through bunching and oiling, and successively through pre-drawing (the temperature of the first hot roll is 145 °C, the speed is 800 m / min, the second hot roll is 145 °C, the speed is 1200 m / min), main drawing (the temperature of the third hot roll is 150 °C, the speed is 4400 m / min), and heat setting (the temperature is 148 °C, the speed is 4400 m / min), and finally wound at 4500 m / min to make the conductive polyester fiber.

[0035] Example 3: This example provides a conductive polyester fiber and its preparation method. The conductive polyester fiber has a skin-core structure. The core layer component in the skin-core structure is the first polyethylene terephthalate, and the skin layer component is composed of the second polyethylene terephthalate, the first polyamide elastomer, and the conductive carbon black masterbatch; Based on the total mass of the conductive polyester fiber being 100%, the skin layer component accounts for 40%, and the core layer component accounts for 60%; Based on the total mass of the cortical component being 100%, the second polyethylene terephthalate accounts for 44%, the first polyamide elastomer accounts for 18%, and the conductive carbon black masterbatch accounts for 38%; The raw materials of the conductive carbon black masterbatch are composed of the second polyamide elastomer and conductive carbon black. In the raw materials of the conductive carbon black masterbatch, conductive carbon black accounts for 50% by mass percentage.

[0036] The first polyethylene terephthalate and the second polyethylene terephthalate are both produced by Jiangsu Guowang Gaoke Fiber Co., Ltd., and their number-average molecular weights are both 25000 g / mol; the first polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the brand number 3070 and a number-average molecular weight of 19000 g / mol; the second polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the brand number 4060 and a number-average molecular weight of 17000 g / mol; The conductive carbon black masterbatch is prepared by the following method: The second polyamide elastomer (brand number 4060) is dried at 100 °C until the moisture content is less than 50 ppm, and then pre-high-speed mixed with conductive carbon black Vulcan® XC72R (oxidation-modified type), and then melt-blended and extruded through a twin-screw extruder, and pelletized by water cooling to obtain the conductive carbon black masterbatch. Among them, the temperatures of the I zone to VII zone of the twin-screw extruder are 178 °C, 190 °C, 215 °C, 213 °C, 213 °C, 210 °C, and 208 °C respectively.

[0037] The preparation method of this conductive polyester fiber includes: The first polyethylene terephthalate and the second polyethylene terephthalate are respectively dried in a low dew-point drying oven at 165 °C until the moisture content is less than 50 ppm; the first polyamide elastomer and the conductive carbon black masterbatch are dried in a low dew-point drying oven at 120 °C until the moisture content is less than 50 ppm; The dried first polyethylene terephthalate serves as the core layer component and is melted by a screw extruder I (the temperatures in zones I - IV are 286°C, 294°C, 293°C, and 293°C respectively), and is metered and extruded by a metering pump I (the temperature of the metering pump is 293°C); the dried second polyethylene terephthalate, the first polyamide elastomer, and the conductive carbon black masterbatch are the skin layer components and are melted by a screw extruder II (the temperatures in zones I - IV are 279°C, 283°C, 280°C, and 280°C respectively), and are metered and extruded by a metering pump II (the temperature of the metering pump is 280°C). The melt of each component is extruded through a skin - core composite spinning component (the temperature of the component is 283°C, where, under this temperature condition, the zero - shear viscosity of the second polyethylene terephthalate is 182 Pa·s higher than that of the second polyamide elastomer, and the zero - shear viscosity of the second polyethylene terephthalate is 166 Pa·s higher than that of the first polyamide elastomer). After cooling by side blowing at 18°C with a wind speed of 0.7 m / s, it undergoes bundling and oiling, and successively passes through pre - drawing (the temperature of the first hot roll is 150°C, the speed is 600 m / min, the second hot roll is 150°C, the speed is 800 m / min), main drawing (the temperature of the third hot roll is 153°C, the speed is 3600 m / min), and heat setting (the temperature is 153°C, the speed is 3600 m / min), and finally is wound at 3650 m / min to produce conductive polyester fiber.

[0038] Example 4: This example provides a conductive polyester fiber and its preparation method. This conductive polyester fiber has a skin - core structure. The core layer component in this skin - core structure is the first polyethylene terephthalate, and the skin layer component is composed of the second polyethylene terephthalate, the first polyamide elastomer, and the conductive carbon black masterbatch; Based on the total mass of the conductive polyester fiber being 100%, the skin layer component accounts for 45% and the core layer component accounts for 55%; Based on the total mass of the skin layer component being 100%, the second polyethylene terephthalate accounts for 46%, the first polyamide elastomer accounts for 19%, and the conductive carbon black masterbatch accounts for 35%; The raw materials of the conductive carbon black masterbatch are composed of the second polyamide elastomer and conductive carbon black. By mass percentage, in the raw materials of the conductive carbon black masterbatch, conductive carbon black accounts for 55%.

[0039] Both the first polyethylene terephthalate and the second polyethylene terephthalate are produced by Jiangsu Guowang Gaoke Fiber Co., Ltd., and their number - average molecular weights are both 28000 g / mol; the first polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., grade 1060, and its number - average molecular weight is 18500 g / mol; the second polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., grade 2040, and its number - average molecular weight is 17500 g / mol; The conductive carbon black masterbatch is prepared by the following method: The second polyamide elastomer (grade 2040) is dried at 100 °C until the moisture content is less than 50 ppm, and then premixed with conductive carbon black Vulcan® XC72R (oxidatively modified type) at high speed. Subsequently, it is melt-blended and extruded through a twin-screw extruder, and then water-cooled and pelletized to obtain the conductive carbon black masterbatch. Among them, the temperatures of zones I - VII of the twin-screw extruder are 178 °C, 190 °C, 217 °C, 214 °C, 214 °C, 212 °C, and 210 °C respectively.

[0040] The preparation method of the conductive polyester fiber includes: The first polyethylene terephthalate and the second polyethylene terephthalate are respectively dried in a low dew point drying oven at 165 °C until the moisture content is less than 50 ppm; the first polyamide elastomer and the conductive carbon black masterbatch are dried in a low dew point drying oven at 120 °C until the moisture content is less than 50 ppm; The dried first polyethylene terephthalate is used as the core layer component and is melted through screw extruder I (the temperatures of zones I - IV are 288 °C, 296 °C, 295 °C, and 295 °C respectively), and is metered and extruded through metering pump I (the temperature of the metering pump is 295 °C); the dried second polyethylene terephthalate, the first polyamide elastomer, and the conductive carbon black masterbatch are used as the skin layer components and are melted through screw extruder II (the temperatures of zones I - IV are 280 °C, 284 °C, 282 °C, and 282 °C respectively), and are metered and extruded through metering pump II (the temperature of the metering pump is 282 °C). The melt of each component is extruded through a skin-core composite spinning component (the temperature of the component is 286 °C. Among them, under this temperature condition, the zero-shear viscosity of the second polyethylene terephthalate is 263 Pa·s higher than that of the second polyamide elastomer, and the zero-shear viscosity of the second polyethylene terephthalate is 246 Pa·s higher than that of the first polyamide elastomer). After being cooled by side blowing at 18 °C with a wind speed of 0.75 m / s, it is oiled during bundling, and then passes through pre-drawing (the temperature of the first hot roller is 153 °C, the speed is 600 m / min, the second hot roller is 153 °C, the speed is 800 m / min), main drawing (the temperature of the third hot roller is 156 °C, the speed is 4200 m / min), and heat setting (the temperature is 155 °C, the speed is 4200 m / min), and finally wound at 4250 m / min to produce the conductive polyester fiber.

[0041] Example 5: This example provides a conductive polyester fiber and its preparation method. The conductive polyester fiber has a skin-core structure. The core layer component in this skin-core structure is the first polyethylene terephthalate, and the skin layer component is composed of the second polyethylene terephthalate, the first polyamide elastomer, and the conductive carbon black masterbatch; Based on the total mass of the conductive polyester fiber being 100%, the skin layer component accounts for 50%, and the core layer component accounts for 50%; Based on the total mass of the cortical component being 100%, the second polyethylene terephthalate accounts for 50%, the first polyamide elastomer accounts for 20%, and the conductive carbon black masterbatch accounts for 30%. The raw materials of the conductive carbon black masterbatch are composed of the second polyamide elastomer and conductive carbon black. In terms of mass percentage, conductive carbon black accounts for 60% in the raw materials of the conductive carbon black masterbatch.

[0042] The first polyethylene terephthalate and the second polyethylene terephthalate are both produced by Jiangsu Guowang Gaoke Fiber Co., Ltd., and the number-average molecular weight is 30000 g / mol; the first polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the grade 6050 and the number-average molecular weight of 18000 g / mol; the second polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the grade 4070 and the number-average molecular weight of 18000 g / mol; The conductive carbon black masterbatch is prepared by the following method: The second polyamide elastomer (grade 4070) is dried at 100 °C until the moisture content is less than 50 ppm, and then pre-high-speed mixed with conductive carbon black Vulcan® XC72R (oxidatively modified type), and then melt-blended and extruded through a twin-screw extruder, and water-cooled pelletized to obtain the conductive masterbatch. Among them, the temperatures of the I zone - VII zone of the twin-screw extruder are 180 °C, 192 °C, 219 °C, 217 °C, 216 °C, 214 °C, and 212 °C respectively.

[0043] The preparation method of this conductive polyester fiber includes: The first polyethylene terephthalate and the second polyethylene terephthalate are respectively dried in a low dew-point drying oven at 165 °C until the moisture content is less than 50 ppm; the first polyamide elastomer and the conductive carbon black masterbatch are dried in a low dew-point drying oven at 120 °C until the moisture content is less than 50 ppm; The dried first ethylene terephthalate serves as the core layer component and is melted by a screw extruder I (the temperatures in zones I - IV are 290°C, 300°C, 298°C, 298°C respectively), and is metered and extruded by a metering pump I (the temperature of the metering pump is 298°C); the dried second polyethylene terephthalate, the first polyamide elastomer, and the conductive carbon black masterbatch serve as the skin layer components, and are melted by a screw extruder II (the temperatures in zones I - IV are 282°C, 285°C, 283°C, 283°C respectively), and are metered and extruded by a metering pump II (the temperature of the metering pump is 283°C). The melts of each component are extruded through a skin - core composite spinning component (the temperature of the component is 290°C. Among them, under this temperature condition, the zero - shear viscosity of the second polyethylene terephthalate is 300 Pa·s higher than that of the second polyamide elastomer, and the zero - shear viscosity of the second polyethylene terephthalate is 278 Pa·s higher than that of the first polyamide elastomer). After being cooled by a side blowing wind at 17°C with a wind speed of 0.75 m / s, through bundling and oiling, it passes through pre - drawing (the temperature of the first hot roller is 155°C, the speed is 600 m / min, the second hot roller is 155°C, the speed is 800 m / min), main drawing (the temperature of the third hot roller is 160°C, the speed is 4800 m / min), heat setting (the temperature is 158°C, the speed is 4800 m / min), and finally wound at 4850 m / min to produce conductive polyester fiber.

[0044] Comparative Example 1: This example provides a conductive polyester elastic fiber and its preparation method, which is basically the same as Example 1, and the only difference is that: the skin layer component consists of the second polyethylene terephthalate and conductive carbon black, and the added mass of the conductive carbon black is the same as that in Example 1, specifically accounting for 45%×40% = 18% of the skin layer component. Correspondingly, the second polyethylene terephthalate accounts for 82% of the skin layer component.

[0045] Comparative Example 2: This example provides a conductive polyester elastic fiber and its preparation method, which is basically the same as Example 1, and the only difference is that: the carbon black used is unmodified ordinary carbon black.

[0046] Comparative Example 3: This example provides a conductive polyester elastic fiber and its preparation method, which is basically the same as Example 1, and the only difference is that: η3 - η1 = 4 Pa·s, η3 - η2 = 16 Pa·s; among them, the first polyethylene terephthalate and the second polyethylene terephthalate are both produced by Jiangsu Guowang Gaoke Fiber Co., Ltd., with a number - average molecular weight of 13000 g / mol; the first polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the brand number 4050 and a number - average molecular weight of 20000 g / mol; the second polyamide elastomer is purchased from Zhejiang Xinyuan Technology Co., Ltd., with the brand number 3060 and a number - average molecular weight of 15000 g / mol.

[0047] Performance Test: The above Examples 1-5 and Comparative Examples 1-3 were subjected to the following performance tests. The specific test results are shown in Table 1.

[0048] The test standard for fineness (dtex) is GB / T 14343-2008 "Test Method for Linear Density of Filament Yarns of Chemical Fibers"; The test standard for volume resistivity (Ω·cm) is FZ / T 50035-2016 "Test Method for Resistance of Synthetic Fiber Filaments"; The test standard for elongation at break (%) is GB / T 14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments"; The test standard for breaking strength (cN / dtex) is GB / T 14344-2022 "Test Method for Tensile Properties of Chemical Fibers - Filaments";

[0049]

[0050] As can be seen from Table 1, compared with Example 1, the volume resistivity of Comparative Example 1 increased significantly (generally, the greater the volume resistivity, the poorer the conductivity), and the elongation at break decreased significantly. It is analyzed that in Example 1 of the present invention, the carrier resin of the conductive carbon black masterbatch is polyamide elastomer, while the skin component of Comparative Example 1 only uses polyethylene terephthalate (PET) blended with it without additionally adding polyamide elastomer, which results in the hindrance of the migration and dispersion of conductive carbon black in the skin layer, and further increases the volume resistivity of the fiber and significantly reduces the conductivity, and the elongation at break also decreases.

[0051] Compared with Example 1, Comparative Example 2 used ordinary unmodified carbon black. The results showed that its volume resistivity increased. It is analyzed that ordinary carbon black lacks surface carboxyl functional groups, and the interfacial interaction between it and polyamide elastomer is significantly weakened, resulting in the difficulty of polyamide elastomer to effectively drive carbon black to migrate and enrich on the fiber surface during melt spinning, ultimately causing the reduction of fiber conductivity (i.e., the increase of volume resistivity).

[0052] Compared with Example 1, the increase rate of volume resistivity in Comparative Example 3 was the strongest. It is analyzed that the zero-shear viscosity difference between the first polyamide elastomer and the second polyamide elastomer and the second polyethylene terephthalate (PET) is insufficient. During melt spinning, the polyamide elastomer is difficult to achieve effective surface migration, resulting in its inability to fully drive conductive carbon black to enrich in the fiber skin layer directionally, and the conductivity of the fiber decreases (i.e., the volume resistivity increases).

[0053] The above embodiments are only for illustrating the technical concept and features of the present invention, and the purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly. However, the protection scope of the present invention cannot be limited thereby. Any equivalent changes or modifications made according to the spirit of the present invention should be covered within the protection scope of the present invention.

[0054] The endpoints and any values disclosed herein are not limited to the exact range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and a single point value, and between single point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

Claims

1. A conductive polyester fiber, characterized in that, The conductive polyester fiber has a skin-core structure. The core layer component in the skin-core structure comprises a first polyethylene terephthalate, and the skin layer component comprises a second polyethylene terephthalate, a first polyamide elastomer and a conductive carbon black masterbatch. The raw materials of the conductive carbon black masterbatch comprise a second polyamide elastomer and conductive carbon black, and the conductive carbon black has terminal carboxyl groups; Under the condition of the same test temperature, the zero-shear viscosity of the first polyamide elastomer is denoted as η1, the zero-shear viscosity of the second polyamide elastomer is denoted as η2, and the zero-shear viscosities of the first polyethylene terephthalate and the second polyethylene terephthalate are both denoted as η3. The zero-shear viscosity is measured by a steady-state shear rheology experiment, and the unit is Pa·s. When the test temperature is 275-290 °C, η1, η2 and η3 satisfy the following conditions: 35 Pa·s ≤ η3 - η1 ≤ 280 Pa·s, 50 Pa·s ≤ η3 - η2 ≤ 300 Pa·s.

2. The conductive polyester fiber according to claim 1, wherein Under the condition of the same test temperature, the zero-shear viscosity of the first polyamide elastomer is greater than or equal to that of the second polyamide elastomer.

3. The conductive polyester fiber according to claim 1 or 2, characterized in that, The number-average molecular weight of the first polyamide elastomer is 18000-20000 g / mol; and / or, the number-average molecular weight of the second polyamide elastomer is 15000-18000 g / mol.

4. The conductive polyester fiber according to claim 1, wherein, Under the condition of the same test temperature, the zero-shear viscosities of the first polyethylene terephthalate and the second polyethylene terephthalate are the same.

5. The conductive polyester fiber according to claim 1 or 4, characterized in that, The number-average molecular weights of the first polyethylene terephthalate and the second polyethylene terephthalate are 20000-30000 g / mol respectively.

6. The conductive polyester fiber according to claim 1, wherein The first polyamide elastomer and the second polyamide elastomer are respectively polyether-based polyamide elastomers.

7. The conductive polyester fiber according to claim 6, characterized in that, The polyether-based polyamide elastomer is composed of a crystalline hard segment and an amorphous soft segment. The crystalline hard segment is polycaprolactam, and the amorphous soft segment is polyethylene glycol.

8. The conductive polyester fiber according to claim 1, wherein Based on the total amount of the skin layer component being 100 parts, the second polyethylene terephthalate accounts for 40-50 parts, the first polyamide elastomer accounts for 15-20 parts, and the conductive carbon black masterbatch accounts for 30-45 parts.

9. The conductive polyester fiber according to claim 1, wherein Based on the total amount of the conductive polyester fiber being 100 parts, the skin layer component accounts for 20-50 parts, and the core layer component accounts for 50-80 parts.

10. The conductive polyester fiber according to claim 1, characterized in that, The conductive carbon black masterbatch is prepared by mixing and extruding a second polyamide elastomer and conductive carbon black; and / or, the particle size of the conductive carbon black is 30-200 nm; and / or, based on the mass percentage, the conductive carbon black accounts for 40%-60% in the raw materials of the conductive carbon black masterbatch.

11. The conductive polyester fiber according to claim 1, wherein, The volume resistivity of the conductive polyester fiber is 30 to 10 4 Ω·cm, the fineness is 1 to 10 dtex, the breaking strength is greater than 3.5 cN / dtex, and the breaking elongation is 15% to 35%.

12. A method for preparing the conductive polyester fiber according to any one of claims 1-11, characterized in that, The preparation method includes: using a melt spinning process to spin the core layer component and the skin layer component into a conductive polyester fiber with a skin-core structure. Among them, the process parameters of spinning and forming include: the melting and extrusion temperature of the core layer component is 285-300 °C, the melting and extrusion temperature of the skin layer component is 270-285 °C, the temperature of the spinning pack is 275-290 °C, the hot drawing temperature is 140-160 °C, and the hot drawing ratio is 5-8 times.

13. Application of the conductive polyester fiber according to any one of claims 1-11 in preparing safety protection materials, camouflage reconnaissance materials, energy harvesting materials, and intelligent wearable materials.

Citation Information

Patent Citations

  • Polyester-polyamide copolymer fiber and manufacturing method thereof

    CN101942708A

  • Polyamide-polyester conductive composite fiber

    CN105544010A

  • Preparation method of conductive polyester fiber

    CN107354534A

  • Polyester-nylon skin-core type industrial yarn and preparation method thereof

    CN117071107A

  • Elastic polyamide fiber and manufacturing method thereof

    CN118422375A